The Impact of Artificial Intelligence Implementation on Business Ethics in Corporate Decision-Making - Sari, Rahmi Rachmawati; Sikki, Nurhaeni; Chintiyani, Fitri; Pusparani, Kinanti Vionanda; Putri, Liska Zahara; Sari, Yulia Puspita; HR, Leni Nuraeni; Depi, Jeanne Nurtami; Nasution, Nurul Fitria (SAFE-Network, 2025)
The integration of artificial intelligence into corporate decision-making processes has introduced complex ethical challenges that demand urgent scholarly and practical attention. This study explores how AI implementation influences business ethics across five key dimensions: algorithmic bias, transparency, responsibility diffusion, privacy, and human autonomy. Employing a qualitative research design, data were collected through in-depth interviews with 25 executives and ethics officers from multinational corporations across diverse sectors. Thematic analysis revealed widespread concerns about the opacity of AI systems, ethical disengagement, and the absence of clear accountability structures. Although some organizations have begun adopting ethical AI governance frameworks, the effectiveness of these measures varies significantly, with many efforts remaining reactive and fragmented. The findings highlight a critical gap between ethical aspirations and organizational realities, emphasizing the need for systemic reforms that embed ethics into the design, deployment, and oversight of AI technologies. This study contributes to the growing body of literature on AI ethics by offering empirical insights and actionable implications for policy, leadership, and future research.